Pedagogical Documentation: A Key for Change and Transformation - Dahlberg, Gunilla; Elfström, Ingela (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2025)
The discourse on pedagogical documentation inspired by the municipal preschools in the Italian city of Reggio Emilia is currently travelling around the world. The fact that this discourse has become so prominent can largely be seen as a resistance towards the reform development that has taken place internationally within the educational system since the 1990s, a reform development linked to global economic competition in the shape of new forms of quality assurance instruments connected to the ideology and policy of neoliberalism. In the article, three constructions of pedagogical documentation are described that can be seen as a form of resistance towards the above educational reforms.